Health education to prevent anemia among adolescents in Samarinda, Indonesia - Ratih Wirapuspita Wisnuwardani; Shelia Wulandari; Annisa Dwi Kartika (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Iron deficiency anemia disrupts the concentration of adolescent girls; reduce their academic achievement, productivity, and physical strength and increases the risk of infection. The nutrition education program about anemia is needed to increase nutritional awareness among students. This community service aim was to evaluate the effectiveness of nutrition education among female students of High School in Samarinda, East Kalimantan, Indonesia. There were two interventions: health education using video among 128 students in in high school and health education using leaflet among 11 students in the boarding school.  A pretest/posttest was conducted to evaluate the knowledge about anemia. Independent sample t-test was used to compare difference between the before and after interventions. Health educations of using video or leaflet increased students’ anemia knowledge. A school health program could improve student’ anemia knowledge. It is very important for school to have collaboration with primary health center, university and other instituions for the health education program. Including nutrition education program to the curriculum of high school is important to prevent malnutrition among female adolescents.